[Letter from National Tobacco Council to Council for Burley Tobacco requesting support in fighting excise taxes] (Tufts Archival Research Center, 2007)
Missing Attachments; Letter from Bruce L. Flye, National Tobacco Council, to William Balden, President of the Council for Burley Tobacco requesting support in the fight against excise taxes. Criticizes excise taxes for negative economic effects, unfairly burdening the poor, and compounding national and state fiscal problems. Asks Balden to encourage his constituents to write letters to federal officials.